THE EFFECT OF OVAPRIM AND hCG INJECTION WITH DIFFERENT DOSES ON OVULATION AND EGG QUALITY OF CLIMBING PEARCH (ANABAS TESTUDINEUS BLOCH) - Irma Yulisari; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
ABSTRACTThe research was conducted from May to June 2017 at The Fish Hatchery and Breeding Laboratory, Fisheries and Marine Faculty University of Riau. The purpose of this research was to evaluate the effect of ovaprim and hCG ovulation and egg quality climbing pearch (Anabas testudineus Bloch) fish. The treatment used in this research was in injection of ovaprim and hCG with different doses is : P1: ovaprim 0,5 ml/kg body weight, P2 : ovaprim 0,7 ml/kg body weight, P3 : hCG 500 IU/kg body weight, P4 : hCG 1000 IU/kg body weight and 1 ml of NaCl physiology 0,9%/kg of body weight. The result showed that ovaprim dose of 0,5 ml/kg of body weight was the bestin turn of latency time of 4,23 hours, total oegg stripping 974 egg/g gonads, egg diameter 0,11 mm, egg maturity 29% and Ovi Somatic Index 25,4%. The temperature ranged from 27-29ºC, pH was 4-6 and DO (Disolved Oxygen) 3,76 ppm.Key word : Ovaprim, hCG, Ovulation, Anabas testudineus Bloch